2012
DOI: 10.1634/theoncologist.2012-0311
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib for the Treatment of ALK-Rearranged Non-Small Cell Lung Cancer: A Success Story to Usher in the Second Decade of Molecular Targeted Therapy in Oncology

Abstract: Crizotinib, an ALK/MET/ROS1 inhibitor, was approved by the U.S. Food and Drug Administration for the treatment of anaplastic lymphoma kinase (ALK)-rearranged non-small cell lung cancer (NSCLC) in August 2011, merely 4 years after the first publication of ALK-rearranged NSCLC. The crizotinib approval was accompanied by the simultaneous approval of an ALK companion diagnostic fluorescent in situ hybridization assay for the detection of ALK-rearranged NSCLC. Crizotinib continued to be developed as an ALK and MET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
155
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(158 citation statements)
references
References 177 publications
3
155
0
Order By: Relevance
“…4,5 Inversions in the short arm of chromosome 2 that juxtapose echinoderm microtubuleassociated protein-like 4 (EML4) with ALK and produce EML4-ALK-fusion tyrosine kinases 4,6 are the most common changes noted. The reported prevalence of ALK rearrangements in unselected NSCLC is approximately 5%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Inversions in the short arm of chromosome 2 that juxtapose echinoderm microtubuleassociated protein-like 4 (EML4) with ALK and produce EML4-ALK-fusion tyrosine kinases 4,6 are the most common changes noted. The reported prevalence of ALK rearrangements in unselected NSCLC is approximately 5%.…”
Section: Introductionmentioning
confidence: 99%
“…Crizotinib-a multitargeted TKI with activity against MET, ALK, [13][14][15] and ROS1 16,17 -was approved by the US Food and Drug Administration in August 2011 for advanced NSCLC positive for ALK rearrangements. 5,[18][19][20] More recently, the randomized phase III PROFILE 1007 trial showed that for previously treated patients with ALK-rearranged NSCLC, crizotinib led to improved outcomes (progression-free survival [PFS; primary outcome], objective response rate [ORR], and quality-of-life measurements) when compared with docetaxel or pemetrexed. 21 The median overall survival (OS) of patients with ALK-rearranged NSCLC from the phase I and II trials (PROFILE 1001 and 1005, respectively) was reported as an unprecedented 29.6 months for 120 patients who continued crizotinib even beyond disease progression (PD).…”
Section: Introductionmentioning
confidence: 99%
“…The five-year survival rate for all stages combined, however, is only 16% [1]. Currently, as a first-line treatment of chemotherapy, several agents clinically approved in targeted therapies for lung cancer have ongoing developments such as bevacizumab (Avastin) [3] and erlotinib (Tarceva), as well as the second generation drugs afatinib (BIBW2992) [4][5] and crizotinib (Xalkori) [6]. However, they still exhibit toxicities and limitations due to the differences in molecular and histological profiles of lung cancers [7].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, several anticancer drugs were developed on the basis of known oncogenic mutations, and the presence of the mutation by itself has been found to be a useful biomarker for these drugs. Examples include some tyrosine kinase inhibitors, including gefitinib and erlotinib, that target epidermal growth factor receptor (EGFR) in NSCLC and for which efficacy depends on the presence of particular EGFR mutations (1,2); crizotinib, which is highly effective when NSCLC cells harbor the EML4-ALK fusion gene (3); and the BRAF inhibitor vemurafenib, which is highly effective when melanoma cells carry the V600E mutation of BRAF (4).…”
Section: Introductionmentioning
confidence: 99%